2018
DOI: 10.1515/cclm-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical implementation of a large-scale online e-learning program on venous blood specimen collection guideline practices

Abstract: Properly designed e-learning programs on VBSC practices supersedes traditional educational programs in usefulness and functionality. Inclusion of questionnaires in the e-learning program is necessary for follow-up of VBSC participant's practices and educational program efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Before students enter the CTC, they need the type of knowledge that can be described as "knowing that"; in other words, the theoretical underpinning and factual knowledge of the relevant practical skill which many nursing students lack (Ravik, 2019). In this study, all students were told to learn factual knowledge before entering the CTC, by reading the literature and the national guidelines (The Handbook of Healthcare, 2021) and by using a web-based educational program including a knowledge exam (Willman et al, 2018). At the CTC, the students were divided into three groups.…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…Before students enter the CTC, they need the type of knowledge that can be described as "knowing that"; in other words, the theoretical underpinning and factual knowledge of the relevant practical skill which many nursing students lack (Ravik, 2019). In this study, all students were told to learn factual knowledge before entering the CTC, by reading the literature and the national guidelines (The Handbook of Healthcare, 2021) and by using a web-based educational program including a knowledge exam (Willman et al, 2018). At the CTC, the students were divided into three groups.…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…However, these articles did not discuss the value of the metrics used in their assessments or exams. For example, participants had to pass an examination to complete the course by achieving 60 percent or more (Carrizosa et al, 2018), while another used a 100 percent pass rate (Willman et al, 2018). Types of assessments varied from multiple-choice questions (e.g., Schulz-Quach et al, 2018;Whitt et al, 2016) to oral assessments (e.g., Elzainy et al, 2020).…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
“…However, the authors identified that the questionnaire had not been previously validated (2018). Studies included those with externally validated questionnaires to measure students' performance (e.g., Kemper, 2017;Willman et al, 2018) and studies which had validated their own questionnaires (e.g., Heuberger et al, 2019;Schulz-Quach et al, 2018). Some questionnaires were specific to their subject content, such as stroke assessment (Gorchs-Molist et al, 2020), drug dispensing (dos Reis et al, 2019), and seizure management (Le Marne et al, 2016) and others measured self-directed learning readiness (Gagnon et al, 2015;Reviriego et al, 2014).…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
“…However, these articles did not discuss the value of the metrics used in their assessments or exams. For example, participants had to pass an examination to complete the course by achieving 60 percent or more (Carrizosa et The Role of Evaluation Methods in Health-Related E-learning: A Rapid Review Online Learning Journal -Volume 26 Issue 4 -December 2022380 al., 2018, while another used a 100 percent pass rate (Willman et al, 2018). Types of assessments varied from multiple-choice questions (e.g., Schulz-Quach et al, 2018;Whitt et al, 2016) to oral assessments (e.g., Elzainy et al, 2020).…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%
“…However, the authors identified that the questionnaire had not been previously validated (2018). Studies included those with externally validated questionnaires to measure students' performance (e.g., Kemper, 2017;Willman et al, 2018) and studies which had validated their own questionnaires (e.g., Heuberger et al, 2019;Schulz-Quach et al, 2018). Some questionnaires were specific to their subject content, such as stroke assessment (Gorchs-Molist et al, 2020), drug dispensing (dos Reis et al, 2019), and seizure management (Le Marne et al, 2016) and others measured self-directed learning readiness (Gagnon et al, 2015;Reviriego et al, 2014).…”
Section: Performance Measures: Assessment Of Knowledgementioning
confidence: 99%